Bad Kitty - Drawn to Trouble (Graphic Novel) Drawn to trouble - Bruel, Nick (New York : Roaring Brook Press, 2022)
Author/illustrator Nick Bruel tries to explain to the reader how to write a story, but Bad Kitty is not at all happy about the plot, which has her going on a turnip diet to lose weight. Includes a recipe for roasted turnips.
Keywords: Bad Kitty -- (Fictitious character from Nick Bruel) -- Juvenile fiction; Bad Kitty -- (Fictitious character from Nick Bruel) -- Fiction; Cats -- Juvenile fiction; Authorship -- Juvenile fiction; Illustration of books -- Juvenile fiction; Cats -- Fiction; Authorship -- Fiction; Illustration of books -- Fiction; Humorous stories; Humorous fiction; Animal fiction